Evaluation of echocardiographic variables in patients of chronic renal failure: pre and post hemodialysis-a single center prospective study - Garg, Gaurav; Vohra, Devinder K.; Kumar, Sharvan; Singh, Ganesh; Srivastava, Alka (International Journal of Advances in Medicine, 2019)
Background: Cardiovascular disease is the leading cause of morbidity and mortality at each stage of Chronic Kidney Disease (CKD) around 30%-45% of patients of stage 5 CKD have advanced cardiovascular complications. Congestive Heart Failure is responsible for approximately 15% death in hemodialysis patients. Hence this study was done with the aim to evaluate the effects of Hemodialysis on various Cardiac parameters detected by 2D Echocardiography in patients with Chronic Kidney Disease. Methods: In this prospective cohort study, 54 patients with Stage 4 and 5 CKD were evaluated for various cardiac parameters by 2D Echocardiography before and after Hemodialysis and detailed characteristics of the patients were analyzed using SPSS version 16 and paired student t-test. Results: Among 54 patients with CKD, 9% (5/54) patients had stage 4 CKD while 91% (49/54) had stage 5 CKD. Hypertension was present in 81.48% (44/54) of patients and Left ventricular hypertrophy was present in 77.77% (42/54). 6 (11%) patients had associated pericardial effusion. Mean Pre and Post Hemodialysis Left ventricular end diastolic diameter (LVIDed) and Left ventricular end systolic diameter (LVIDes) was 50.38±4.16mm and 48.91±4.14mm; 33.54±3.29 mm and 32.58±2.80 mm respectively which was statistically significant (p <0.001). Pre-HD Left atrial diameter was 34.20±3.81mm and it became 33.19±3.30mm Post-HD (p <0.001). Left ventricular mass index (LVMI) was 136.70±35.91 g/m2 pre-HD and 125.54±29.35 g/m2 post-HD which is significant. Left Ventricular Ejection Fraction was 47.34±5.72% before HD and it became 48.82±4.56% after 6 session of Hemodialysis over 3 weeks which is statistically significant (p<0.038). Conclusions: The present findings suggest patients with Stage 4 and 5 CKD who were on hemodialysis there was significant improvement in various cardiac parameters apart from increase in left ventricular ejection fraction, which may lead to decrease morbidity and mortality in these patients.